تعليم اللغة العربية لغير الناطقين بها اعتمادا علي الليسانيات التطبيقية - شعيب، مڤنونبف (جامعة أحمد دراية أدرار - مخبر المخطوطات الجزائرية في إفريقيا, 2021)
لا يمكن تعليم اللغة العربية لغير الناطقين بها إلا وفق منهج علمي مُعد على أسس واضحة وبطريقة منظمة ومكون من عناصر محددة، مع تحديد أهدافه وتطوير الاستراتيجيات المناسبة له. إلى جانب ذلك كله وجود المعلم الكفء الذي يعد الأساس في عملية التعليم، ومدى دوره في مواجهة متطلبات العصر المتغير. لذلك قصدنا بالطريقة المتبعة في تعليم اللغة العربية لغير الناطقين بها، هي الخطة الشاملة التي يستعين بها المدرس على تحقيق الأهداف المطلوبة من تعلم اللغة وتتضمن الطريقة ما يتبعه المدرس من أساليب وإجراءات، وما يستخدمه من مادة تعليمية ووسائل معينة. وهناك كثير من الطرائق التي تعلم بها اللغات الأجنبية، وليس من بينها ما يمكن وصفه بالطريقة المثلى التي تلائم كل الطلاب في مختلف البيئات والظروف؛ فلكل طريقة أوجه تميز، ونقاط ضعف، وعلى المدرس أن يلم بتلك الطرائق ويصطفي ما يتماشى مع المواقف التعليمية التي تعترضه.
Arabic language can be taught to non-native speakers, only according to a scientific method developed on clear foundations and in an organized manner and made up of specific elements, by defining its objectives and developing appropriate strategies for it. Besides, there is a competent teacher who is considered the basis of the educational process, and the extent of his role in facing the requirements of the changing era. That is why our purpose for the method used to teach Arabic to non-native speakers, is the comprehensive plan that the teacher uses to achieve the required goals of learning the language. The method includes the approaches and procedures used by the teacher, and the educational material and methods he uses. There are many ways in which foreign languages are learned, none of them can be described as the ideal one that suits all students in different settings and circumstances. So each method has distinctions and weaknesses, and teacher has to be familiar with these methods and choose what is in line with the educational situations that hinder him.
Keywords: اللغة العربية -- الناطقين بغير العربية -- البحث العلمي